Lagrangian study of the low-level flow field over the Indian Ocean during the summer monsoon - CADET, DANIEL; OLORY-TOGBE , PAUL; SOMMERIA, GILLES (MAUSAM, 1978)
A new tool has been developed for Lagrangian study of the Planetary Boundary Layer over long distances. During the summer of 1975, 45 low-level superpressure balloons were launched from the Seychelles Islands for flights within the tropical boundary layer over the Indian Ocean. The balloons were located by the Nimbus-6 satellite which also relayed pressure measurements made aboard the balloons.The experiment provided very adequate Lagrangian trajectories up to 10 days, which have shown the different regimes of the monsoon. The main results are summarized. They clearly prove the large range of possibilities offered by low-level balloons to map air currents and complement other types of meteorological data, especially in sparse coverage areas. The Laboratoire da Meteorolgie Dynamique plans a new and larger experiment for the MONEX period in 1979. A brief account of its scientific and experimental objectives is given.